Bullous Pemphigoid: A Series Of 50 Cases - Tatiana Miyuki Iida; Taila Yuri Siqueira Machado; Adriana Maria Porro (Brazilian Society of Geriatrics and Gerontology, 2024)
OBJECTIVES: This study aims to analyze data on the epidemiology, treatment and course of bullous pemphigoid in 50 patients and compare findings to the data already available in the literature. METHODS: Data were collected retrospectively through medical records and analyzed statistically. A review of the literature was conducted using articles indexed in the MEDLINE (via PubMed) database. RESULTS: The mean age at diagnosis was 71.1 years. Comorbidities were observed in almost all cases, and the association between bullous pemphigoid and neurological diseases was present in 18% of patients, in agreement with recent data in the literature. CONCLUSION: Care of comorbidities, especially neurological diseases, which increase the mortality of patients with bullous pemphigoid, is thus essential.